http://www.google.co.uk/search?hl=en&safe=off&rlz=1G1GGLQ_ENUK354&q=(2^3)+-+(2+x+(-4))+-+(4+x+(-3)^2)&aq=f&aqi=&aql=&oq=&gs_rfai=

OP should look in here: http://www.wolframalpha.com/examples/Math.html Must be going back to school tomorrow.

hmm i get 124 8 - -8 - -108 = 8+8+108 = 124 EDIT: my bad lemme work it out again yeh got -20, for some reason i thought it was cubed for C, wtf was i thinking?

a=2, b=-4, c=-3 a³ - 2b - 4c² As before, start with the "Not thinking" line: 2³ -8x(-4) -4x(-3)² now sort out the numbers: 8 not 6!!!! It's 2x2x2 = 4x2 = 8 + 32 minus times a minus is a plus - 36 do it carefully, (-3)² = +9, -4x9 = -36 = 4 This is the explanation on a website my daughter has been pointed to by her teacher.

Come on people this isn't hard at all! I'll even put it into words! 2 cubed is 8 2 times -4 is -8 -3 squared is 9, and 9 x 4 is 36 8 take away negative 8 is 16. 16 take away 36 is -20 That was simples.

Its not my expression, I don't understand where that comes from either, it is on the website that my daughter was pointed to. It looks wrong to me also.